Hair shaft disorders in children - An update - Yasmeen Jabeen Bhat; Taiba Trumboo; Kewal Krishan (Wolters Kluwer Medknow Publications, 2023)
Disorders of hair shaft are a diverse group of congenital and acquired abnormalities of the hair that can pose a diagnostic and therapeutic challenge to the dermatologists. Hair shaft abnormalities can occur as an isolated phenomenon or can be associated with an underlying genetic syndrome. Any change in the texture, appearance, and growth of the hair should prompt evaluation of the patient for the presence of any hair shaft anomaly. The diagnosis can be suggested by a complete history and physical examination of the hair-bearing areas as well as other ectodermal structures (nails and teeth). A key feature in the evaluation of hair shaft defects is to determine the fragility of the hair shaft that can be elucidated by performing the "tug test." Trichoscopy and light microscopy serve as valuable tools in establishing the specific type of hair shaft disorder. An update of the approach for the diagnosis and management is included in this review.